Hydrogen plasma treatment of silicon thin-film structures and nanostructured layers - Nazarov, A.N.; Lysenko, V.S.; Nazarova, T.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
The review concentrates on the analysis of the RF hydrogen plasma effect on thin-film metal-dioxide-silicon and silicon-dioxide silicon structures which are a modern basis of micro- and nanoelectronics. The especial attention is paid to athermic mechanisms of transformation of defects in dioxide, SiO₂-Si interface and SiO₂-Si nanocrystal ones and thin layers of silicon; atomic hydrogen influence on the annealing of vacancy defects and the implanted impurity activation in a subsurface implanted silicon layer; and the hydrogen plasma effect on luminescent properties of nanostructured light emitting materials.